Characterization and Assessment of PEEK/Silicon Dioxide Composite - Husam Mohammed Saeed; Raghdaa Kareem Jassim (International Journal of Dentistry)
Background. In the domain of dentistry, PEEK materials have been utilised as removable partial denture frameworks, implant substances, and fixed dental prostheses. Even though PEEK polymer has a low modulus of elasticity, its mechanical attributes could be fine-tuned by integrating various inorganic filler materials. The study intends to characterise and assess Nano SiO2/PEEK composite prepared by using the melt blend approach. Materials and Methods. The design of this study uses 3% SiO2 and PEEK composite made using the melt blend technique and studies their characteristics with reference to pure PEEK. The following assessments are conducted: SEM and EDX assessment with AFM investigation in addition to tensile strength test, transverse strength test, and wettability test. All data were scrutinised by SPSS software version 24 and the statistical analyses included the mean, standard deviation, and the independent sample t-test. Results. The outcomes of this investigation pertain to the differences in characteristics of a composite of SiO2/PEEK compared with pure PEEK. The outcomes indicate that there is a statistically highly significant increase in the mean value of transverse strength was seen with the PEEK/SiO2 composite (3503.02 MPa) versus PEEK (2694.61 MPa), while there is a statistically significant decrease in the mean value of the tensile strength for PEEK/SiO2 (63.69 MPa) versus PEEK (97.62 MPa). Moreover, improvement in hydrophobic characteristics and surface roughness of PEEK/SiO2 (81.78°), (0.66 nm) versus PEEK (71.01°), (1.23 nm), respectively, thus giving more chance to composite to be investigated in human bone/implant substitution. Furthermore, the results of EDX and SEM images exhibited adequate distribution of Nano SiO2 within the PEEK matrix. There was also a statistically substantial decrease in the surface roughness and tensile strength obtained from the AFM investigation. Conclusion. As far as this study is concerned, a conclusion can be made that we can use 3% Nano SiO2 to prepare a composite of SiO2/PEEK by using the melt blend approach. Nano SiO2 can alter the SiO2/PEEK composite’s transverse strength and reduce the hydrophobic characteristics of the surfaces with proper distribution of nanoparticles within the matrix of PEEK with less surface roughness.